High-toughness halogen-free flame-retardant crosslinked cable and preparation method thereof
By mixing high-density polyethylene, ethylene-vinyl acetate copolymer, modified MXene and additives and crosslinking it through ultraviolet radiation, combined with protective coatings of self-healing polyurethane emulsion, the problems of flammability and mechanical properties of existing cables are solved, and crosslinked cables with high flame retardant, high toughness and water resistance are achieved.
Patent Information
- Application Number
- CN202510000363.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Existing crosslinked polyolefin cables are flammable, and the mechanical properties of the materials are deteriorated after adding inorganic flame retardant, and are susceptible to external forces to cause insulation abrasions and damage, affecting service life.
Crosslinked ingredients are prepared by mixing high-density polyethylene, ethylene-vinyl acetate copolymer, modified MXene and additives. Crosslinking is formed by crosslinking by ultraviolet radiation, and protective coating prepared by self-healing polyurethane emulsion is coated on the surface to form a protective layer sleeve.
It improves the flame retardancy, toughness and water resistance of the cable, extends the service life of the cable, and has both high flame retardancy and high toughness.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to a high-toughness halogen-free flame-retardant cross-linked cable and a preparation method thereof. Background Art
[0002] With the progress of society, safety awareness and environmental protection concepts have been deeply rooted in people's minds. People's attention has shifted from traditional polyvinyl chloride cables to low-smoke environmentally friendly cables. Polyolefins with good mechanical properties, electrical properties, chemical stability and good processing performance are increasingly used in cables, and the performance of cross-linked polyolefins has been improved.
[0003] Cross-linked polyolefin is an important raw material for existing cables, but most of the polyolefins commonly used in cables are flammable materials. When encountering external fire sources or internal faults, cross-linked polyolefin cables are very easy to burn. The existing market usually adds inorganic flame retardants, such as magnesium hydroxide, aluminum hydroxide and other metal hydroxides to improve the flame retardancy of cables, but highly filled metal hydroxides will deteriorate the mechanical properties of the material. At the same time, the laying of the cable is easily affected by external forces, causing insulation abrasions and damage, which affects the service life of the cable. Summary of the invention
[0004] The object of the present invention is to provide a high-toughness halogen-free flame-retardant cross-linked cable and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a high-toughness halogen-free flame-retardant cross-linked cable comprises the following steps: S1: mixing high-density polyethylene, ethylene-vinyl acetate copolymer, modified MXene and additives to obtain a cross-linking ingredient; S2: Extruding and coating the cross-linked ingredients on a mold, and cross-linking them by ultraviolet irradiation to obtain a reinforcement layer; S3: preparing a protective coating by blending the self-healing polyurethane emulsion, modified MXene and photoinitiator; S4: coating the protective coating on the surface of the reinforcing layer, light curing, and drying to form a protective layer to obtain a protective layer cover; S5: The outer surface of the wire core is sequentially wrapped with a mica tape layer and a fiber layer, and then a protective layer sleeve is sheathed to obtain a high-toughness halogen-free flame-retardant cross-linked cable.
[0006] Furthermore, the wire core is a copper core.
[0007] Furthermore, the fiber layer is one of glass fiber, basalt fiber and aramid fiber.
[0008] Furthermore, the working conditions of the light curing treatment are: irradiation with light having a wavelength of 365 nm for 8 minutes.
[0009] Furthermore, the composition of the cross-linking ingredients is, by weight: 77-87 parts of high-density polyethylene, 8-13 parts of ethylene-vinyl acetate copolymer, 3-6 parts of modified MXene, and 2-4 parts of additives.
[0010] Furthermore, the auxiliary agent is a photoinitiator and a cross-linking auxiliary agent compounded in a mass ratio of 4:1.
[0011] Furthermore, the protective coating is composed of 2-5 parts of modified MXene, 21-31 parts of self-healing polyurethane emulsion, and 0.5-1 part of photoinitiator, in parts by mass.
[0012] Furthermore, the working conditions of the UV irradiation cross-linking are as follows: the sample is placed on the conveyor belt of the UV irradiation equipment with a power of 1641 mW / cm² and a speed of 0.8 cm / s, and is fully irradiated 5 times.
[0013] Furthermore, the preparation of the composite MXene includes the following steps: (1) Mix MXene and Tris-HCl buffer, ultrasonically treat for 15-20 min, add a mixture of dopamine hydrochloride and Tris-HCl buffer, ultrasonically treat for 10-15 min, stir in a 18-25 ° C water bath for 10-12 h, wash, centrifuge, freeze-dry, and grind to obtain dopamine-coated MXene; (2) Mix dopamine-coated MXene, imidazole, and dichloromethane, add a mixture of tert-butyldimethylsilyl chloride and dichloromethane, stir at 18-25° C. for 12-16 h, extract and wash 2-3 times with sodium bicarbonate aqueous solution, deionized water, and saturated sodium chloride solution, dry, and rotary evaporate to obtain an intermediate preparation; (3) DOPO and chloroform are mixed, and carbon tetrachloride and triethylamine are added in an ice bath environment, and a mixture of the intermediate preparation and chloroform is added, and the mixture is stirred for 12-16 hours, and the mixture is washed with a saturated sodium chloride solution and deionized water for 3-4 times, extracted, dried, and concentrated, and purified by silica gel column chromatography using a volume ratio of 1:1 petroleum ether and ethyl acetate, rotary evaporated, dried, tetrahydrofuran, and tetrabutylammonium fluoride solution, and stirred at 18-25°C for 12-16 hours, extracted, washed, and concentrated, and purified by silica gel column chromatography using a volume ratio of 1:1 methanol and ethyl acetate to obtain a composite MXene; (4) Under a nitrogen atmosphere, the composite MXene, N,N-dimethylformamide, and potassium carbonate are mixed, allyl chloride is added, and the mixture is kept warm at 40-60°C for 10-12 h. Toluene is added, and the mixture is washed with sodium chloride solution for 3-5 times, and separated to obtain a modified MXene.
[0014] Furthermore, the preparation of the self-repairing polyurethane emulsion comprises the following steps: Under nitrogen protection, 4,4'-dicyclohexylmethane diisocyanate, polytetrahydrofuran, polydimethylsiloxane diol and dibutyltin dilaurate are mixed and kept warm at 78-82°C for 1-2 hours to obtain a prepolymer; a mixed solution of 2,2-dihydroxymethylpropionic acid and dimethylacetamide is added, and the mixture is kept warm for 1-2 hours, a chain extender containing borate bonds and disulfide bonds and a mixed solution of dimethylacetamide are added, the temperature is lowered to 58-62°C and stirred for 1-2 hours, pentaerythritol triacrylate and p-hydroxyanisole are added, and the mixture is stirred for 1-2 hours, the temperature is lowered to 30-35°C, triethylamine is added, and the mixture is stirred for 15-30 minutes, deionized water is added for emulsification, and rotary evaporation is performed to obtain a self-healing waterborne polyurethane emulsion with a solid content of 35-40%.
[0015] Furthermore, the mass ratio of 4,4'-dicyclohexylmethane diisocyanate, polytetrahydrofuran, polydimethylsiloxane diol, 2,2-dihydroxymethylpropionic acid, a chain extender containing a borate bond and a disulfide bond, and pentaerythritol triacrylate is 3.2:2.2:0.5:0.5:0.6:1.6.
[0016] Further, the preparation of the chain extender containing borate ester bond and disulfide bond comprises the following steps: 1) Mix 3-carboxyphenylboronic acid and PBS buffer, add N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide in sequence, keep warm at 18-25°C for 15-20 minutes, add cystamine hydrochloride, keep warm for 15-20 minutes, increase the temperature to 40-50°C and keep warm for 8-10 minutes, keep warm at 18-25°C for 10-12 hours, wash with water, centrifuge and dry to obtain (3-dihydroxyborylbenzoic acid)cystamine; 2) Mix (3-dihydroxyborylbenzoic acid) cystamine, 1,2,6-hexanetriol and tetrahydrofuran, add anhydrous magnesium sulfate, stir at 18-25° C. for 22-24 hours, filter, add n-hexane and dry to obtain a chain extender containing borate ester bonds and disulfide bonds.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a high-toughness halogen-free flame-retardant cross-linked cable and a preparation method thereof. Through component and process design, a cross-linked cable with high toughness, good water resistance, a self-repairing surface, and halogen-free and high flame retardancy is prepared, which greatly prolongs the service life of the cross-linked cable.
[0018] High-density polyethylene, ethylene-vinyl acetate copolymer, modified MXene, and additives are mixed and co-extruded, and ultraviolet radiation cross-linking is used to prepare the reinforcement layer of the cable. The additive is a compound of a photoinitiator and a cross-linking additive. MXene is introduced into the reinforcement layer as a flame retardant. In order to improve the uniformity of MXene dispersion and flame retardancy in the cross-linking ingredients, MXene is modified. MXene is first coated with dopamine, and catechol groups that play a role in quenching free radicals in gas phase flame retardancy and have a certain carbonization ability in the condensed phase are introduced on its surface. In order to protect the catechol groups, tert-butyl The MXene is treated with dimethylsilyl chloride and then DOPO is grafted onto its surface using amino groups to greatly improve its flame retardancy. It is then treated with tetrabutylammonium fluoride solution to obtain a composite MXene containing both catechol groups and PN bonds. This composite MXene is added to cables to greatly improve the flame retardancy and smoke suppression of the cables. In order to improve the interfacial compatibility of MXene and high-density polyethylene, the composite MXene is reacted with allyl chloride under alkaline conditions to introduce double bonds into the composite MXene, which increases the complexity of the cross-linking network during irradiation cross-linking, thereby greatly improving the toughness of the reinforcement layer, making it have both high flame retardancy and high toughness.
[0019] In order to improve the mechanical damage resistance of the cable, the present invention adopts a self-repairing polyurethane emulsion, a modified MXene, and a photoinitiator to prepare a protective coating, and the protective coating is coated on the surface of the reinforcement layer, and a photocuring treatment is performed to prepare a water-resistant and corrosion-resistant protective layer sleeve with a self-repairing surface; In the preparation of self-healing polyurethane emulsion, 4,4'-dicyclohexylmethane diisocyanate, polytetrahydrofuran and polydimethylsiloxane diol are used as raw materials, and the prepolymer is synthesized under the action of dibutyltin dilaurate catalyst. The introduction of polydimethylsiloxane diol greatly improves the water resistance of the protective layer, 2,2-dihydroxymethylpropionic acid is added as a hydrophilic chain extender, a chain extender containing borate ester bonds and disulfide bonds is added as a chain extender of multiple dynamic reversible bonds, pentaerythritol triacrylate is used as a photosensitizer, p-hydroxyanisole is used as an inhibitor, triethylamine is used as a neutralizer, and deionized water emulsion is added. A self-healing water-based polyurethane emulsion is obtained by chemical reaction; the chain extender containing borate ester bonds and disulfide bonds is synthesized by the coupling reaction of 1-ethyl-(3-dimethylaminopropyl)carbodiimide / N-hydroxysuccinimide to obtain (3-dihydroxyborylbenzoic acid) cystamine containing diphenylboronic acid groups and disulfide bonds, which is then synthesized by the condensation of phenylboronic acid groups with 1,2,6-hexanetriol to give the cable self-healing properties; modified MXene is used as filler in the protective coating to greatly improve the flame retardancy, water resistance and corrosion resistance of the cable, thereby greatly extending the service life of the cable. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0022] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0023] Embodiment 1: A method for preparing a high-toughness halogen-free flame-retardant cross-linked cable, comprising the following steps: S1: mixing high-density polyethylene, ethylene-vinyl acetate copolymer, modified MXene and additives to obtain a cross-linking ingredient; In terms of mass parts, the composition of the cross-linking ingredients is: 77 parts of high-density polyethylene, 8 parts of ethylene-vinyl acetate copolymer, 3 parts of modified MXene, and 2 parts of auxiliary agent; The auxiliary agent is a photoinitiator and a cross-linking auxiliary agent mixed in a mass ratio of 4:1; The preparation of the modified MXene comprises the following steps: (1) 0.6 g MXene and 100 mL Tris-HCl buffer were mixed and ultrasonically treated for 15 min. A mixture of 1.4 g dopamine hydrochloride and 200 mL Tris-HCl buffer was added and ultrasonically treated for 10 min. The mixture was stirred at 600 r / min for 10 h in a 18 °C water bath, washed, centrifuged, freeze-dried, and ground to obtain dopamine-coated MXene. (2) 4 g dopamine-coated MXene, 5.7 g imidazole, and 60 mL dichloromethane were mixed, and a mixture of 8 g tert-butyldimethylsilyl chloride and 70 mL dichloromethane was added, stirred at 18 °C for 16 h, extracted and washed twice with sodium bicarbonate aqueous solution, deionized water, and saturated sodium chloride solution, dried, and rotary evaporated to obtain an intermediate preparation; (3) Mix 2.7g DOPO and 50mL chloroform, add 2.1g carbon tetrachloride and 1.4g triethylamine in an ice bath environment, add 4.7g intermediate preparation and 50mL chloroform mixture, stir for 12h, wash with saturated sodium chloride solution and deionized water three times, extract, dry and concentrate, purify by silica gel column chromatography with petroleum ether and ethyl acetate in a volume ratio of 1:1, rotary evaporate and dry, add 30mL tetrahydrofuran, add 40mL1mol / L tetrabutylammonium fluoride solution, stir at 18°C for 16h, extract, wash and concentrate, purify by silica gel column chromatography with methanol and ethyl acetate in a volume ratio of 1:1 to obtain composite MXene; (4) Under a nitrogen atmosphere, 40 g of composite MXene, 40 mL of N,N-dimethylformamide, and 2 g of potassium carbonate were mixed, 5 g of allyl chloride was added, and the mixture was kept at 40 °C for 12 h. 40 mL of toluene was added, and the mixture was washed three times with sodium chloride solution and separated to obtain modified MXene. S2: Extruding and coating the cross-linked ingredients on a mold, and cross-linking them by ultraviolet irradiation to obtain a reinforcement layer; Place the sample on a 365nm single-wavelength LED UV irradiation array, with a power of 1641mW / cm² and a speed of 0.8cm / s, on the conveyor belt of the UV irradiation equipment, and fully irradiate for 5 times; S3: preparing a protective coating by blending the self-healing polyurethane emulsion, modified MXene and photoinitiator; The composition of the protective coating is, by mass, 2 parts of modified MXene, 21 parts of self-healing polyurethane emulsion, and 0.5 parts of photoinitiator; The preparation of the self-repairing polyurethane emulsion comprises the following steps: Under nitrogen protection, 3.2g 4,4'-dicyclohexylmethane diisocyanate, 2.2g polytetrahydrofuran, 0.5g polydimethylsiloxane diol, and 2 drops of dibutyltin dilaurate were mixed and kept at 78°C for 2h to obtain a prepolymer; 0.5g 2,2-dihydroxymethylpropionic acid and a mixed solution of 5mL dimethylacetamide were added, and the mixture was kept warm for 1h, 0.6g of a chain extender containing borate bonds and disulfide bonds and a mixed solution of 5mL dimethylacetamide were added, the temperature was lowered to 58°C and stirred for 2h, 1.6g pentaerythritol triacrylate and 5mg p-hydroxyanisole were added, and the mixture was stirred for 1h, the temperature was lowered to 30°C, 0.5g triethylamine was added, and the mixture was stirred for 15min, deionized water was added for emulsification, and rotary evaporation was performed to obtain a self-healing polyurethane emulsion with a solid content of 38%; The preparation of the chain extender containing borate ester bond and disulfide bond comprises the following steps: 1) Mix 1.7 g 3-carboxyphenylboronic acid and 100 mL PBS buffer, add 1.4 g N-hydroxysuccinimide and 1.5 g 1-ethyl-(3-dimethylaminopropyl)carbodiimide in sequence, keep warm at 18°C for 20 min, add 0.9 g cystamine hydrochloride, keep warm for 15 min, increase the temperature to 40°C and keep warm for 10 min, keep warm at 18°C for 12 h, wash with water, centrifuge and dry to obtain (3-dihydroxyborylbenzoic acid) cystamine; 2) Mix 4.2 g (3-dihydroxyborylbenzoic acid) cystamine, 10 g 1,2,6-hexanetriol, and 50 mL tetrahydrofuran, add 10 g anhydrous magnesium sulfate, stir at 18 ° C for 24 h, filter, add 600 mL n-hexane, and dry to obtain a chain extender containing borate ester bonds and disulfide bonds; S4: coating the protective coating on the surface of the reinforcing layer, light curing, and drying to form a protective layer to obtain a protective layer cover; The working conditions of the light curing treatment were: irradiation with light of wavelength 365 nm for 8 min; S5: The outer surface of the wire core is wrapped with a mica tape layer and a fiber layer in sequence, and then a protective layer is sheathed to obtain a high-toughness halogen-free flame-retardant cross-linked cable; the wire core is a copper core; and the fiber layer is glass fiber.
[0024] Embodiment 2: A method for preparing a high-toughness halogen-free flame-retardant cross-linked cable, comprising the following steps: S1: mixing high-density polyethylene, ethylene-vinyl acetate copolymer, modified MXene and additives to obtain a cross-linking ingredient; In terms of mass parts, the composition of the cross-linking ingredients is: 83 parts of high-density polyethylene, 10 parts of ethylene-vinyl acetate copolymer, 4 parts of modified MXene, and 3 parts of auxiliary agent; The auxiliary agent is a photoinitiator and a cross-linking auxiliary agent mixed in a mass ratio of 4:1; The preparation of the modified MXene comprises the following steps: (1) 0.6 g MXene and 100 mL Tris-HCl buffer were mixed and ultrasonically treated for 18 min. A mixture of 1.4 g dopamine hydrochloride and 200 mL Tris-HCl buffer was added and ultrasonically treated for 13 min. The mixture was stirred at 600 r / min for 11 h in a 20 °C water bath, washed, centrifuged, freeze-dried, and ground to obtain dopamine-coated MXene. (2) 4 g dopamine-coated MXene, 5.7 g imidazole, and 60 mL dichloromethane were mixed, and a mixture of 8 g tert-butyldimethylsilyl chloride and 70 mL dichloromethane was added, and the mixture was stirred at 20 °C for 14 h, extracted and washed twice with sodium bicarbonate aqueous solution, deionized water, and saturated sodium chloride solution, dried, and rotary evaporated to obtain an intermediate preparation; (3) Mix 2.7g DOPO and 50mL chloroform, add 2.1g carbon tetrachloride and 1.4g triethylamine in an ice bath environment, add 4.7g intermediate preparation and 50mL chloroform mixture, stir for 14h, wash with saturated sodium chloride solution and deionized water three times, extract, dry and concentrate, purify by silica gel column chromatography with petroleum ether and ethyl acetate in a volume ratio of 1:1, rotary evaporation and drying, add 30mL tetrahydrofuran, add 40mL1mol / L tetrabutylammonium fluoride solution, stir at 20℃ for 14h, extract, wash and concentrate, purify by silica gel column chromatography with methanol and ethyl acetate in a volume ratio of 1:1 to obtain composite MXene; (4) Under a nitrogen atmosphere, 40 g of composite MXene, 40 mL of N,N-dimethylformamide, and 2 g of potassium carbonate were mixed, 5 g of allyl chloride was added, and the mixture was kept at 60 °C for 11 h. 40 mL of toluene was added, and the mixture was washed with sodium chloride solution for 4 times and separated to obtain modified MXene. S2: Extruding and coating the cross-linked ingredients on a mold, and cross-linking them by ultraviolet irradiation to obtain a reinforcement layer; Place the sample on a 365nm single-wavelength LED UV irradiation array, with a power of 1641mW / cm² and a speed of 0.8cm / s, on the conveyor belt of the UV irradiation equipment, and fully irradiate for 5 times; S3: preparing a protective coating by blending the self-healing polyurethane emulsion, modified MXene and photoinitiator; The composition of the protective coating is, by weight: 4 parts of modified MXene, 27 parts of self-healing polyurethane emulsion, and 0.8 parts of photoinitiator; The preparation of the self-repairing polyurethane emulsion comprises the following steps: Under nitrogen protection, 3.2g 4,4'-dicyclohexylmethane diisocyanate, 2.2g polytetrahydrofuran, 0.5g polydimethylsiloxane diol, and 2 drops of dibutyltin dilaurate were mixed and kept at 80°C for 1.5h to obtain a prepolymer; 0.5g 2,2-dihydroxymethylpropionic acid and a mixed solution of 5mL dimethylacetamide were added, and the mixture was kept warm for 1.5h, 0.6g of a chain extender containing borate bonds and disulfide bonds and a mixed solution of 5mL dimethylacetamide were added, the temperature was lowered to 60°C and stirred for 1.5h, 1.6g pentaerythritol triacrylate and 5mg p-hydroxyanisole were added, and the mixture was stirred for 1.5h, the temperature was lowered to 33°C, 0.5g triethylamine was added, and the mixture was stirred for 20min, deionized water was added for emulsification, and rotary evaporation was performed to obtain a self-healing polyurethane emulsion with a solid content of 38%; The preparation of the chain extender containing borate ester bond and disulfide bond comprises the following steps: 1) Mix 1.7 g 3-carboxyphenylboronic acid and 100 mL PBS buffer, add 1.4 g N-hydroxysuccinimide and 1.5 g 1-ethyl-(3-dimethylaminopropyl)carbodiimide in sequence, keep warm at 20°C for 18 min, add 0.9 g cystamine hydrochloride, keep warm for 18 min, heat to 45°C for 9 min, keep warm at 20°C for 11 h, wash with water, centrifuge and dry to obtain (3-dihydroxyborylbenzoic acid) cystamine; 2) Mix 4.2 g (3-dihydroxyborylbenzoic acid) cystamine, 10 g 1,2,6-hexanetriol, and 50 mL tetrahydrofuran, add 10 g anhydrous magnesium sulfate, stir at 20 ° C for 23 h, filter, add 600 mL n-hexane, and dry to obtain a chain extender containing borate ester bonds and disulfide bonds; S4: coating the protective coating on the surface of the reinforcing layer, light curing, and drying to form a protective layer to obtain a protective layer cover; The working conditions of the light curing treatment were: irradiation with light of wavelength 365 nm for 8 min; S5: The outer surface of the wire core is wrapped with a mica tape layer and a fiber layer in sequence, and then a protective layer is sheathed to obtain a high-toughness halogen-free flame-retardant cross-linked cable; the wire core is a copper core; and the fiber layer is glass fiber.
[0025] Embodiment 3: A method for preparing a high-toughness halogen-free flame-retardant cross-linked cable, comprising the following steps: S1: mixing high-density polyethylene, ethylene-vinyl acetate copolymer, modified MXene and additives to obtain a cross-linking ingredient; In terms of mass parts, the composition of the cross-linking ingredients is: 87 parts of high-density polyethylene, 13 parts of ethylene-vinyl acetate copolymer, 6 parts of modified MXene, and 4 parts of additives; The auxiliary agent is a photoinitiator and a cross-linking auxiliary agent mixed in a mass ratio of 4:1; The preparation of the modified MXene comprises the following steps: (1) 0.6 g MXene and 100 mL Tris-HCl buffer were mixed and ultrasonically treated for 20 min. A mixture of 1.4 g dopamine hydrochloride and 200 mL Tris-HCl buffer was added and ultrasonically treated for 15 min. The mixture was stirred at 600 r / min for 12 h in a 25 °C water bath, washed, centrifuged, freeze-dried, and ground to obtain dopamine-coated MXene. (2) 4 g dopamine-coated MXene, 5.7 g imidazole, and 60 mL dichloromethane were mixed, and a mixture of 8 g tert-butyldimethylsilyl chloride and 70 mL dichloromethane was added, stirred at 25 °C for 12 h, extracted and washed three times with sodium bicarbonate aqueous solution, deionized water, and saturated sodium chloride solution, dried, and rotary evaporated to obtain an intermediate preparation; (3) 2.7 g DOPO and 50 mL chloroform were mixed, and 2.1 g carbon tetrachloride and 1.4 g triethylamine were added in an ice bath environment. A mixture of 4.7 g intermediate preparation and 50 mL chloroform was added, and the mixture was stirred for 16 h. The mixture was washed with saturated sodium chloride solution and deionized water for 4 times, extracted, dried, and concentrated. The mixture was purified by silica gel column chromatography using a volume ratio of 1:1 petroleum ether and ethyl acetate. The mixture was rotary evaporated and dried, and 30 mL tetrahydrofuran was added. 40 mL 1 mol / L tetrabutylammonium fluoride solution was added, and the mixture was stirred at 25 °C for 12 h. The mixture was extracted, washed, and concentrated. The mixture was purified by silica gel column chromatography using a volume ratio of 1:1 methanol and ethyl acetate to obtain a composite MXene. (4) Under a nitrogen atmosphere, 40 g of composite MXene, 40 mL of N,N-dimethylformamide, and 2 g of potassium carbonate were mixed, 5 g of allyl chloride was added, and the mixture was kept at 80 °C for 10 h. 40 mL of toluene was added, and the mixture was washed with sodium chloride solution for 5 times and separated to obtain modified MXene. S2: Extruding and coating the cross-linked ingredients on a mold, and cross-linking them by ultraviolet irradiation to obtain a reinforcement layer; Place the sample on a 365nm single-wavelength LED UV irradiation array, with a power of 1641mW / cm² and a speed of 0.8cm / s, on the conveyor belt of the UV irradiation equipment, and fully irradiate for 5 times; S3: preparing a protective coating by blending the self-healing polyurethane emulsion, modified MXene and photoinitiator; The composition of the protective coating is, by weight: 5 parts of modified MXene, 31 parts of self-healing polyurethane emulsion, and 1 part of photoinitiator; The preparation of the self-repairing polyurethane emulsion comprises the following steps: Under nitrogen protection, 3.2g 4,4'-dicyclohexylmethane diisocyanate, 2.2g polytetrahydrofuran, 0.5g polydimethylsiloxane diol, and 2 drops of dibutyltin dilaurate were mixed and kept warm at 82°C for 1h to obtain a prepolymer; 0.5g 2,2-dihydroxymethylpropionic acid and a mixed solution of 5mL dimethylacetamide were added, and the mixture was kept warm for 2h, 0.6g of a chain extender containing borate bonds and disulfide bonds and a mixed solution of 5mL dimethylacetamide were added, the temperature was lowered to 62°C and stirred for 1h, 1.6g pentaerythritol triacrylate and 5mg p-hydroxyanisole were added, and the mixture was stirred for 2h, the temperature was lowered to 35°C, 0.5g triethylamine was added, and the mixture was stirred for 30min, deionized water was added for emulsification, and rotary evaporation was performed to obtain a self-healing polyurethane emulsion with a solid content of 38%; The preparation of the chain extender containing borate ester bond and disulfide bond comprises the following steps: 1) Mix 1.7 g 3-carboxyphenylboronic acid and 100 mL PBS buffer, add 1.4 g N-hydroxysuccinimide and 1.5 g 1-ethyl-(3-dimethylaminopropyl)carbodiimide in sequence, keep warm at 25°C for 15 min, add 0.9 g cystamine hydrochloride, keep warm for 20 min, raise the temperature to 50°C and keep warm for 8 min, keep warm at 25°C for 10 h, wash with water, centrifuge and dry to obtain (3-dihydroxyborylbenzoic acid) cystamine; 2) Mix 4.2 g (3-dihydroxyborylbenzoic acid) cystamine, 10 g 1,2,6-hexanetriol, and 50 mL tetrahydrofuran, add 10 g anhydrous magnesium sulfate, stir at 25 ° C for 22 h, filter, add 600 mL n-hexane, and dry to obtain a chain extender containing borate ester bonds and disulfide bonds; S4: coating the protective coating on the surface of the reinforcement layer, light curing, and drying to obtain a protective layer cover; The working conditions of the light curing treatment were: irradiation with light of wavelength 365 nm for 8 min; S5: The outer surface of the wire core is wrapped with a mica tape layer and a fiber layer in sequence, and then a protective layer is sheathed to obtain a high-toughness halogen-free flame-retardant cross-linked cable; the wire core is a copper core; and the fiber layer is glass fiber.
[0026] Comparative Example 1: Taking Example 3 as the control group, MXene was used to replace the modified MXene, and the other processes were normal.
[0027] Comparative Example 2: Example 3 was used as a control group, and a chain extender containing a borate ester bond and a disulfide bond was not prepared, and other processes were normal.
[0028] The preparation of MXene in the examples and comparative examples includes the following steps: 0.5 g Ti3AlC2, 0.78 g lithium fluoride, and 10 mL of 37% concentrated hydrochloric acid were mixed, kept at 36 °C for 22 h, washed, centrifuged, the pH was adjusted to 6.8, 40 mL of deionized water was added, ultrasonicated for 25 min, and centrifuged to obtain MXene.
[0029] In the embodiment and the comparative example, the thickness of the fiber layer is 1 mm, the thickness of the reinforcement layer is 2 mm, and the thickness of the protective layer is 500 μm.
[0030] Sources of raw materials used (for demonstration purposes only): High-density polyethylene HDPE: Dongguan Jinshixiang Plastic Raw Materials Co., Ltd.; Ethylene-vinyl acetate copolymer (99%, industrial grade): Hubei Rishengchang New Materials Technology Co., Ltd.; Mica tape (single-sided gold mica tape, thickness 0.14mm): Changzhou Zhongnan Electronic Technology Co., Ltd.; Glass fiber cloth EW250F (0.25mm): Sinoma Science and Technology Co., Ltd.; Cross-linking aid (trimethylallyl isocyanate) 01106: Wuhan Kanos Technology Co., Ltd.; Imidazole S30365, tert-butyldimethylsilyl chloride S4382 4. DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) S46419: Shanghai Yuanye Biotechnology Co., Ltd.; polydimethylsiloxane diol 08778: Wuhan Shuer Biotechnology Co., Ltd.; p-Hydroxyanisole 150-76-5: Jinan Century Tongda Chemical Co., Ltd.; photoinitiator (benzophenone 119-61-9): Suzhou Senfida Chemical Co., Ltd.; 1,2,6-hexanetriol 106-69-4: Hubei Jiangmin Taihua Chemical Co., Ltd.; Tris-HCl buffer T30 1494, dopamine hydrochloride D103111, tetrahydrofuran T431413, triethylamine T103285, Ti3AlC2 T302678, lithium fluoride L434127, dibutyltin dilaurate D100274, polytetrahydrofuran P118599, N,N-dimethylformamide D111999, tetrabutylammonium fluoride T100870, allyl chloride A103821, 4,4'-dicyclohexylmethane diisocyanate D155475, 2,2-dihydroxymethylpropionic acid B104539, dimethylacetyl Amine D108096, pentaerythritol triacrylate P189117, 3-carboxyphenylboronic acid C103261, PBS buffer B478425, N-hydroxysuccinimide H109330, 1-ethyl-(3-dimethylaminopropyl)carbodiimide E106172, cystamine hydrochloride C597659: Aladdin reagent; anhydrous magnesium sulfate, n-hexane, hydrochloric acid, dichloromethane, sodium bicarbonate, sodium chloride, chloroform, carbon tetrachloride, petroleum ether, ethyl acetate, methanol, potassium carbonate, toluene, analytical grade: Sinopharm reagent.
[0031] Performance test: The protective layer sleeves prepared in the embodiments and comparative examples were tested: Impact strength test: The sample size is 80mm×10mm, the notch width is 2mm, refer to ISO180 standard, use cantilever beam impact tester to test notch impact strength at 25℃; Flame retardancy: refer to GB / T2408-2008 vertical combustion test flame retardancy grade; Self-repairing property: scratch the surface of the protective layer with a length of 1mm, a depth of 500µm and a width of 2µm, keep it at 30℃ for 12h, and observe the scratch length with an electron microscope. The self-repairing rate = (L 初始划痕长度 -L 现有划痕长度) / L 初始划痕长度 ×100%; Corrosion resistance: Soak the protective layer in 4g / L sodium chloride solution for 2 weeks and observe the surface condition. If there is no change on the surface, it is qualified; the test results are as follows; Table 1
[0032] The present invention provides a high-toughness halogen-free flame-retardant cross-linked cable and a preparation method thereof. Through component and process design, a cross-linked cable with high toughness, good water resistance, a self-repairing surface, and halogen-free and high flame retardancy is prepared, which greatly prolongs the service life of the cross-linked cable. In Table 1, / indicates that the item has not been tested.
[0033] By comparing Example 3 with Comparative Example 1, it can be seen that high-density polyethylene, ethylene-vinyl acetate copolymer, modified MXene, and additives are mixed and co-extruded, and ultraviolet radiation cross-linking is used to prepare the reinforcement layer of the cable, wherein the additive is a compound of a photoinitiator and a cross-linking additive, and MXene is introduced into the reinforcement layer as a flame retardant. In order to improve the uniformity of dispersion and flame retardancy of MXene in the cross-linking ingredients, MXene is modified. MXene is first coated with dopamine, and catechol groups that play a role in quenching free radicals in gas phase flame retardancy and also have a certain carbonization ability in the condensed phase are introduced on its surface. In order to further For protection, it is first treated with tert-butyldimethylsilyl chloride, and then DOPO is grafted with its surface amino group to greatly improve its flame retardancy. It is then treated with tetrabutylammonium fluoride solution to obtain a composite MXene containing both catechol groups and PN bonds. This composite MXene is added to the cable to greatly improve the flame retardancy and smoke suppression of the cable. In order to improve the interfacial compatibility of MXene and high-density polyethylene, the composite MXene is reacted with allyl chloride under alkaline conditions to introduce double bonds on the composite MXene, which increases the complexity of the cross-linking network during irradiation cross-linking, thereby greatly improving the toughness of the reinforcement layer, making it have both high flame retardancy and high toughness.
[0034] By comparing Example 3 with Comparative Example 2, it can be seen that in the preparation of the self-repairing polyurethane emulsion, 4,4'-dicyclohexylmethane diisocyanate, polytetrahydrofuran, and polydimethylsiloxane diol are used as raw materials, and the prepolymer is synthesized under the action of the catalyst dibutyltin dilaurate. The introduction of polydimethylsiloxane diol greatly improves the water resistance of the protective layer, 2,2-dihydroxymethylpropionic acid is added as a hydrophilic chain extender, and a chain extender containing a borate ester bond and a disulfide bond is added as a chain extender of multiple dynamic reversible bonds. Pentaerythritol triacrylate is used as a photosensitizer, p-hydroxyanisole is used as an inhibitor, and triethylamine is used as a neutralizer. and an agent, and deionized water is added for emulsification to obtain a self-healing water-based polyurethane emulsion; the chain extender containing a borate ester bond and a disulfide bond is a (3-dihydroxyborylbenzoic acid) cystamine containing a bisphenylboronic acid group and a disulfide bond synthesized by a 1-ethyl-(3-dimethylaminopropyl)carbodiimide / N-hydroxysuccinimide coupling reaction, and then synthesized by a condensation reaction of a phenylboronic acid group with a cis-dihydroxy group to give the cable self-healing properties; modified MXene is used as a filler in the protective coating to greatly improve the flame retardancy, water resistance and corrosion resistance of the cable, thereby greatly extending the service life of the cable.
[0035] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a high-toughness halogen-free flame-retardant cross-linked cable, characterized in that: The following steps are involved: S1: mixing high-density polyethylene, ethylene-vinyl acetate copolymer, modified MXene and additives to obtain a cross-linking ingredient; S2: Extruding and coating the cross-linked ingredients on a mold, and cross-linking them by ultraviolet irradiation to obtain a reinforcement layer; S3: preparing a protective coating by blending the self-healing polyurethane emulsion, modified MXene and photoinitiator; S4: coating the protective coating on the surface of the reinforcing layer, light curing, and drying to form a protective layer to obtain a protective layer cover; S5: The outer surface of the wire core is sequentially wrapped with a mica tape layer and a fiber layer, and then a protective layer sleeve is sheathed to obtain a high-toughness halogen-free flame-retardant cross-linked cable.
2. The method for preparing a high-toughness halogen-free flame-retardant cross-linked cable according to claim 1, characterized in that: In terms of mass fractions, the cross-linking ingredients are composed of 77-87 parts of high-density polyethylene, 8-13 parts of ethylene-vinyl acetate copolymer, 3-6 parts of modified MXene, and 2-4 parts of additives.
3. The method for preparing a high-toughness halogen-free flame-retardant cross-linked cable according to claim 1, characterized in that: The auxiliary agent is a photoinitiator and a cross-linking auxiliary agent mixed in a mass ratio of 4:
1.
4. The method for preparing a high-toughness halogen-free flame-retardant cross-linked cable according to claim 1, characterized in that: The protective coating is composed of 2-5 parts of modified MXene, 21-31 parts of self-healing polyurethane emulsion, and 0.5-1 part of photoinitiator in parts by mass.
5. The method for preparing a high-toughness halogen-free flame-retardant cross-linked cable according to claim 1, characterized in that: The working conditions of UV irradiation cross-linking are as follows: the sample is placed on the conveyor belt of the UV irradiation equipment with a power of 1641mW / cm² and a speed of 0.8cm / s, and is fully irradiated 5 times.
6. The method for preparing a high-toughness halogen-free flame-retardant cross-linked cable according to claim 1, characterized in that: The preparation of the modified MXene comprises the following steps: (1) Mix MXene and Tris-HCl buffer, ultrasonically treat for 15-20 min, add a mixture of dopamine hydrochloride and Tris-HCl buffer, ultrasonically treat for 10-15 min, stir in a 18-25 ° C water bath for 10-12 h, wash, centrifuge, freeze-dry, and grind to obtain dopamine-coated MXene; (2) Mix dopamine-coated MXene, imidazole, and dichloromethane, add a mixture of tert-butyldimethylsilyl chloride and dichloromethane, stir at 18-25° C. for 12-16 h, extract and wash 2-3 times with sodium bicarbonate aqueous solution, deionized water, and saturated sodium chloride solution, dry, and rotary evaporate to obtain an intermediate preparation; (3) DOPO and chloroform are mixed, and carbon tetrachloride and triethylamine are added in an ice bath environment, and a mixture of the intermediate preparation and chloroform is added, and the mixture is stirred for 12-16 hours, and the mixture is washed with a saturated sodium chloride solution and deionized water for 3-4 times, extracted, dried, and concentrated, and purified by silica gel column chromatography using a volume ratio of 1:1 petroleum ether and ethyl acetate, rotary evaporated, dried, tetrahydrofuran, and tetrabutylammonium fluoride solution, and stirred at 18-25°C for 12-16 hours, extracted, washed, and concentrated, and purified by silica gel column chromatography using a volume ratio of 1:1 methanol and ethyl acetate to obtain a composite MXene; (4) Under a nitrogen atmosphere, the composite MXene, N,N-dimethylformamide, and potassium carbonate are mixed, allyl chloride is added, and the mixture is kept warm at 40-60°C for 10-12 h. Toluene is added, and the mixture is washed with sodium chloride solution for 3-5 times, and separated to obtain a modified MXene.
7. The method for preparing a high-toughness halogen-free flame-retardant cross-linked cable according to claim 1, characterized in that: The preparation of the self-repairing polyurethane emulsion comprises the following steps: Under nitrogen protection, 4,4'-dicyclohexylmethane diisocyanate, polytetrahydrofuran, polydimethylsiloxane diol and dibutyltin dilaurate are mixed and kept warm at 78-82°C for 1-2 hours to obtain a prepolymer; a mixed solution of 2,2-dihydroxymethylpropionic acid and dimethylacetamide is added, and the mixture is kept warm for 1-2 hours, a chain extender containing borate bonds and disulfide bonds and a mixed solution of dimethylacetamide are added, the temperature is lowered to 58-62°C and stirred for 1-2 hours, pentaerythritol triacrylate and p-hydroxyanisole are added, and the mixture is stirred for 1-2 hours, the temperature is lowered to 30-35°C, triethylamine is added, and the mixture is stirred for 15-30 minutes, deionized water is added for emulsification, and the mixture is rotary evaporated to obtain a self-healing polyurethane emulsion.
8. The method for preparing a high-toughness halogen-free flame-retardant cross-linked cable according to claim 7, characterized in that: The mass ratio of 4,4'-dicyclohexylmethane diisocyanate, polytetrahydrofuran, polydimethylsiloxane diol, 2,2-dihydroxymethylpropionic acid, a chain extender containing a borate bond and a disulfide bond, and pentaerythritol triacrylate is 3.2:2.2:0.5:0.5:0.6:1.
6.
9. The method for preparing a high-toughness halogen-free flame-retardant cross-linked cable according to claim 7, characterized in that: The preparation of the chain extender containing borate ester bond and disulfide bond comprises the following steps: 1) Mix 3-carboxyphenylboronic acid and PBS buffer, add N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide in sequence, keep warm at 18-25°C for 15-20 minutes, add cystamine hydrochloride, keep warm for 15-20 minutes, increase the temperature to 40-50°C and keep warm for 8-10 minutes, keep warm at 18-25°C for 10-12 hours, wash with water, centrifuge and dry to obtain (3-dihydroxyborylbenzoic acid)cystamine; 2) Mix (3-dihydroxyborylbenzoic acid) cystamine, 1,2,6-hexanetriol and tetrahydrofuran, add anhydrous magnesium sulfate, stir at 18-25° C. for 22-24 hours, filter, add n-hexane, and dry to obtain a chain extender containing borate ester bonds and disulfide bonds.
10. A high-toughness halogen-free flame-retardant cross-linked cable, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Prepration method of nanometer material capable of improving fire resistance of waterborne polyurethane coating and adhesive
CN104449325A
Long-life low-smoke flame-retardant cotton covered wire and preparation process thereof
CN116435028A
Processing technology of high-temperature-resistant waterproof cable
CN118248414A
Cited By
High-performance multifunctional cable and preparation method thereof
CN120854050A
Anti-adsorption coating for dry powder online mixing equipment pipeline and preparation method of anti-adsorption coating
CN121136589A
Tensile steel-cored aluminum stranded wire
CN121393991A